Comparative Genomics Reveal the Animal-Associated Features of the Acanthopleuribacteraceae Bacteria, and Description of Sulfidibacter corallicola gen. nov., sp., nov. - Wang, Guanghua; Li, Yuanjin; Liu, Jianfeng; Chen, Biao; Su, Hongfei; Liang, Jiayuan; Huang, Wen; Yu, Kefu (Frontiers in Microbiology, 2022)
Members of the phylum Acidobacteria are ubiquitous in various environments. Soil acidobacteria have been reported to present a variety of strategies for their success in terrestrial environments. However, owing to lack of pure culture, information on animal-associated acidobacteria are limited, except for those obtained from 16S rRNA genes. To date, only two acidobacteria have been isolated from animals, namely strain M133T obtained from coral Porites lutea and Acanthopleuribacter pedis KCTC 12899T isolated from chiton. Genomics and physiological characteristics of strain M133T and A. pedis KCTC 12899T were compared with 19 other isolates (one strain from each genus) in the phylum Acidobacteria. The results revealed that strain M133T represents a new species in a new genus in the family Acanthopleuribacteraceae. To date, these two Acanthopleuribacteraceae isolates have the largest genomes (10.85–11.79 Mb) in the phylum Acidobacteria. Horizontal gene transfer and gene duplication influenced the structure and plasticity of these large genomes. Dissimilatory nitrate reduction and abundant secondary metabolite biosynthetic gene clusters (including eicosapentaenoic acid de novo biosynthesis) are two distinct features of the Acanthopleuribacteraceae bacteria in the phylum Acidobacteria. The absence of glycoside hydrolases involved in plant polysaccharide degradation and presence of animal disease-related peptidases indicate that these bacteria have evolved to adapt to the animal hosts. In addition to low- and high-affinity respiratory oxygen reductases, enzymes for nitrate to nitrogen, and sulfhydrogenase were also detected in strain M133T, suggesting the capacity and flexibility to grow in aerobic and anaerobic environments. This study highlighted the differences in genome structure, carbohydrate and protein utilization, respiration, and secondary metabolism between animal-associated acidobacteria and other acidobacteria, especially the soil acidobacteria, displaying flexibility and versatility of the animal-associated acidobacteria in environmental adaption.